Approximation algorithms for profit maximisation in multicast D2D networks. (28th January 2021) - Bhat, Jagadeesha R.; Sheu, Jang-Ping; Hon, Wing-Kai; Yang, Cian-You
As the demand for mobile data services increases, telecom companies need to develop wise strategies to retain existing customers. For instance, in a multicast scenario, satisfying individual user's quality of service (QoS), data demand at varying rates, etc. are complicated tasks. Earlier works on device-to-device (D2D) multicast have majorly discussed the cases of throughput maximisation without considering the individual user's data request rates. In this paper, we propose two algorithms to maximise the telecom operator's profit collected from the users in a two-hop D2D multicast network, when users have different channel qualities and data request rates while receiving multicast data through a single transmission session. First, we model our multicast scheme for the proposed scenario as a budgeted maximum coverage problem. Later, we propose two approximation algorithms that guarantee approximation ratios of 1−1/ √ e and 1 − 1 / e, respectively, where e denotes the base of the natural logarithm. Numerical results show that the proposed algorithms perform better than the other candidate algorithms and nearly approximates the optimal solution.